Un panorama historique illustré des égouts parisiens aux Archives de Paris - Ronan Bouttier; Nicolas Courtin (In Situ)
In 2018 the Paris archive service recovered a unique collection of graphic documents relating to the sewers of the capital at the end of the nineteenth century. The collection contains a series of plans retracing the history of the sewage system since the seventeenth century. Above all, however, the collection’s treasures are its cross-sections of the capital’s throughfares showing life above ground, in about 1900, as well as the underground networks of sewers, canals, railways, gas mains, etc. The maps and watercolours were used as promotion material for the capital’s sanitation services, presented at the 1900 universal exhibition, an initiative that was both pedagogical and self-satisfied. Our article aims at outlining a contextual approach to the history of how these documents were created and an explanation for the considerable attention that the municipal services paid them, at least until the beginning of the twenty-first century when they were almost completely forgotten. The large-format documents have now been digitised and can now be consulted anew.